Étudier l’accueil des neurosciences en éducation : une illustration épistémologique à partir de la positivismusstreit - Arianne Robichaud; Marina SCHWIMMER; Maxime GAUTHIER-LACASSE (Éducation et Socialisation)
The introduction of neurosciences in education gives rise to animated reactions. As some embrace the arrival of such science with open arms, others tend to be more skeptical. This article submits fundemental thoughts regarding this debate, inspired by its parallels with the positivism dispute, one of the most important epistemological debates of the 20th century. This paper is divided in three distinct sections : first, we present the principal epistemological postures at the heart of the actual debate regarding the introduction of neurosciences in education ; we then retrace the most notable aspects of the positivism dispute which opposed Adorno and Habermas to Popper and Albert, and its similarities with the present debate. Finally, we propose a way by which we could continue the actual debate, starting from a more constructive perspective.